A historical analysis of the social and cultural significance of stairs and stair designs - Esguerra, Divina Oliva Villegas (1998.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Stairs -- Philippines; Stair building